The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.11591/ijece.v7i6.pp2950-2957
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of a Two-stage Sagnac loop filter using Jones Matrices

Abstract: In this work, a theoretical analysis of a Sagnac loop filter (SLF) with twostage polarization maintaining fibers (PMFs) and polarization controllers (PCs) is presented. The transmission function of this two-stage SLF is calculated in detail by using Jones matrix. The calculation is performed in order to investigate the filtering characteristics. The theoretical results show that the wavelength interval is depending on the dynamic settings of the length of the PMFs and the polarization angle of the PCs. By chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Some geometrical coefficients like a thickness of metal and substrate; the hole diameter also the number of periodic holes and metal properties can effect on EOT spectra because the surface plasmons that will be excited by incident light is affected by changing the size of hole and it have been confirmed that any change in the size of the holes lead to a small variations in transmission efficiency and peak [11][12][13][14][15]. Je Hong provided that the transmission characteristics is a function of film thickness of metallic hole array samples which is prepared with different hole periodicity, size and shape on a silica substrate and shows highly transmission efficiency at small thickness of gold metal [16,17]. Plasmonic nanostructures have been extensively investigated both for scientific interest in their unique optical properties and for practical applications, such as optoelectronic devices, sensors, biomedical treatment; and so on [18,19].…”
Section: Introductionmentioning
confidence: 90%
“…Some geometrical coefficients like a thickness of metal and substrate; the hole diameter also the number of periodic holes and metal properties can effect on EOT spectra because the surface plasmons that will be excited by incident light is affected by changing the size of hole and it have been confirmed that any change in the size of the holes lead to a small variations in transmission efficiency and peak [11][12][13][14][15]. Je Hong provided that the transmission characteristics is a function of film thickness of metallic hole array samples which is prepared with different hole periodicity, size and shape on a silica substrate and shows highly transmission efficiency at small thickness of gold metal [16,17]. Plasmonic nanostructures have been extensively investigated both for scientific interest in their unique optical properties and for practical applications, such as optoelectronic devices, sensors, biomedical treatment; and so on [18,19].…”
Section: Introductionmentioning
confidence: 90%
“…MWFL has become one of the main attractions in photonics research communities. The type of comb filters that have been used for multiwavelength generation are Fabry-perot filter [1], Mach Zehnder interferometer [2], Lyot filter [3,4] and array waveguide grating [5] and two-stage Sagnac loop filter [6]. Lyot filter-based MWFL is an attractive choice for multiple laser generation due to its qualities such as low optical loss and simple structure.…”
Section: Introductionmentioning
confidence: 99%